2014
DOI: 10.1016/j.pneurobio.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning provides neuroprotection in models of CNS disease: Paradigms and clinical significance

Abstract: Preconditioning is a phenomenon in which brief episodes of a sublethal insult induce robust protection against subsequent lethal injuries. Preconditioning has been observed in multiple organisms and can occur in the brain as well as other tissues. Extensive animal studies suggest that the brain can be preconditioned to resist acute injuries, such as ischemic stroke, neonatal hypoxia/ischemia, trauma, and agents that are used in models of neurodegenerative diseases, such as Parkinson’s disease and Alzheimer’s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 421 publications
6
142
1
Order By: Relevance
“…However, our finding that the severity of injury is not increased when ischemia is induced only 4 h after exposure to LPS is in contrast to the finding of sensitization to HI injury in the neonatal rat [18]. This difference is likely to reflect the repeated LPS exposure in the present study resulting in some degree of self-tolerance and cross-tolerance, as observed in a variety of models of brain injury [67]. …”
Section: Discussioncontrasting
confidence: 73%
“…However, our finding that the severity of injury is not increased when ischemia is induced only 4 h after exposure to LPS is in contrast to the finding of sensitization to HI injury in the neonatal rat [18]. This difference is likely to reflect the repeated LPS exposure in the present study resulting in some degree of self-tolerance and cross-tolerance, as observed in a variety of models of brain injury [67]. …”
Section: Discussioncontrasting
confidence: 73%
“…These findings of course are related to discrete events, whereas in the present study, stable, mild hypoxia was present for 24 h or more before cerebral ischaemia, which is well within the typical interval required to induce preconditioning [22] . Given that fetal body weight was less in the pre-existing hypoxia group, it is very likely that relative placental restriction was present compared to normoxic animals.…”
Section: Discussionsupporting
confidence: 65%
“…Nowadays, growing data suggested that non-pharmaceutical therapies might provide new approaches for stroke [7][8][9]. Ischemic postconditioning (IPost), in which repeated brief episodes of sublethal ischemia/reperfusion are applied after lethal ischemic episode and during reperfusion, has emerged as a promising method against I/R injury.…”
Section: Introductionmentioning
confidence: 99%